The mechanism and clinical significance of FKBP5 gene DNA methylation in various psychiatric, metabolic and tumor-related diseases - Wang, Changliang; Xia, Zhixiu (Frontiers in Genetics, 2026)
The FK506 Binding Protein 5 (FKBP5) gene encodes a protein that binds to the immunosuppressive agent FK506. FKBP5 expression is regulated by genetic variation and epigenetic mechanisms, including DNA methylation (DNAm). This gene regulates the glucocorticoid receptor (GR), and aberrant FKBP5 methylation is associated with psychiatric and metabolic disorders. Recent evidence also indicates that FKBP5 methylation significantly influences malignant tumors. The methylation status of FKBP5 not only modulates its own expression but also contributes to disease pathogenesis by regulating downstream signaling pathways. Despite extensive research on FKBP5 in individual disease contexts, a critical gap remains in understanding how its DNAm serves as a unifying epigenetic mechanism across psychiatric, metabolic, and neoplastic disorders. Existing reviews often focus on single disease domains or on genetic and protein-level regulation, lacking a systematic, horizontal integration analysis centered on DNAm—a dynamic and reversible modification. This review aims to fill this gap by proposing a coherent “epigenetic regulatory framework” that elucidates how tissue-and site-specific FKBP5 DNAm patterns, through modulating glucocorticoid (GC) signaling, stress responses, and inflammatory pathways (e.g., NF-κB), contribute to divergent pathological outcomes. By integrating evidence from disparate fields, this review summarizes the role of FKBP5 DNAm in disease biology, its functions across various disorders, and its potential as a biomarker and therapeutic target, aiming to provide a theoretical foundation and strategic insights for disease diagnosis and treatment.